Construction and Influencing Factors of Voluntary Compensation Subjects for Herders—From the Perspective of Sustainable Utilization of Grassland Resources - Liu, Yuchen; Zhang, Xinling; Deng, Hankun (Sustainability, 2024)
The grassland ecological compensation mechanism is a basic guarantee for promoting the sustainable utilization of grassland resources, and the reasonable determination of the compensation subject is the basic premise for the effective operation of the grassland ecological compensation mechanism. At present, grassland ecological compensation is mainly based on government compensation, and the compensation method generally adopted is financial transfer payment with a single source of compensation funds. Therefore, establishing diversified compensation entities is of great significance in expanding the sources of compensation funds. As important users of grassland resources, herders should become the main representatives of grassland ecological compensation according to the principle of “whoever uses, pays”. In this study, based on survey data with respect to pastoral areas in Inner Mongolia, we used a multivariate ordered logistic regression model to empirically analyze the factors influencing the establishment of a voluntary compensation entity for herders. The results of this study showed that (1) the resource endowment factors of the respondents, including livestock inventory, grazing area, and cutting grassland area, have a significant positive impact on the willingness of herdsmen to voluntarily serve as the main representatives of grassland ecological compensation. When each influencing factor increased by one unit, the probability of voluntarily becoming a compensation subject increased by 3.5%, 1.91%, and 1.41%, respectively. (2) The factor of prohibited pasture area in the endowment of herders had a significant negative effect on their willingness to become compensation subjects, which indicates that the larger the prohibited pasture area owned by herders, the lower their grassland utilization rate and the lower their willingness to voluntarily become compensation subjects. (3) Among the cognitive factors of the respondents, “whether they will continue to support the implementation of the grassland compensation policy” had a positive promoting effect on herdsmen voluntarily becoming compensation subjects, showing that the higher the support of herdsmen for the ecological compensation system, the more willing they were to become compensation subjects. This article is based on the perspective of the sustainable utilization of grassland resources and empirically analyzes the influencing factors of herders’ willingness to reduce their number of livestock. Through the voluntary reduction of livestock by herders, a voluntary compensation entity for herders is constructed. Based on the research conclusions, relevant countermeasures and suggestions are proposed, providing a reference for improving grassland ecological compensation policies and promoting the sustainable utilization of grassland resources.